2023
DOI: 10.1097/tp.0000000000004469
|View full text |Cite
|
Sign up to set email alerts
|

CD40-CD40L Blockade: Update on Novel Investigational Therapeutics for Transplantation

Abstract: Effective immune responses require antigen presentation by major histocompatibility complexes with cognate T-cell receptor and antigen-independent costimulatory signaling for T-cell activation, proliferation, and differentiation. Among several costimulatory signals, CD40-CD40L is of special interest to the transplantation community because it plays a vital role in controlling or regulating humoral and cellular immunity. Blockade of this pathway has demonstrated inhibition of donor-reactive T-cell responses and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 79 publications
(179 reference statements)
0
3
0
Order By: Relevance
“…Conversely, another study showed that CD40L was associated with markers of inflammation, it did not independently serve as a risk marker for stroke ( 33 ). In addition, severe immunosuppression and unexpected thromboembolic events have been reported in preclinical and clinical trials involving anti-CD40L ( 34 , 35 ). However, these observational associations are insufficient to establish a causal relationship between CD40 and stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, another study showed that CD40L was associated with markers of inflammation, it did not independently serve as a risk marker for stroke ( 33 ). In addition, severe immunosuppression and unexpected thromboembolic events have been reported in preclinical and clinical trials involving anti-CD40L ( 34 , 35 ). However, these observational associations are insufficient to establish a causal relationship between CD40 and stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the CD28-CD80/86 costimulatory pathways, other therapeutics targeting the CD40-CD154 costimulatory pathway are also in preclinical study and have shown special promise as the cornerstone of immunosuppression in several preclinical xenotransplant models, 125 and early phase efforts in kidney allotransplantation persist with Fc modified agents that do not precipitate platelet aggregation or thrombosis ( ClinicalTrials.gov NCT05027906). The most notable of these studies is a phase 2a trial evaluating dual costimulation blockade with dazodalibep (Fc silent CD40L protein antagonist, VIB4920 or HZN4920) and belatacept with thymoglobulin induction for prophylaxis of kidney allograft rejection (NCT04046549).…”
Section: The Pastmentioning
confidence: 99%
“… 8, 9 ), other important steps for successful cardiac xenotransplantation involve perfusion preservation of the pig hearts, 10 non‐nephrotoxic immunosuppression of the recipients involving T cell co‐stimulation blockade ( 1 ; reviewed in ref. 11 ), and controlling the post‐transplantation growth of the pig hearts (reviewed in refs. 9, 12 ).…”
Section: Introductionmentioning
confidence: 99%